Psychosocial Support Assessment among Women Police force in India - Ashifa, K.M. (International Journal of Psychosocial Rehabilitation, 2019)
Women are an integral part of our society, but they are not given proper treatment in society. They are prone to a lot of discrimination and violence since they are not aware of the steps to be taken against these acts. But some women go a step forward and try to approach police stations for justice. For this purpose, all women police stations were launched in early 1938 to create a fear-free approach mind for women to raise a voice against violence and discrimination. After the emergence of women police, the normal women are enjoying a safe and secure life. For the past two decades, the state of Tamil Nadu, India, has established All-Women Police Stations (AWPS) to focus exclusively on crimes against women (Srinivasan, 2013) Women police work for others welfare; they face lot of issues and problems and themselves in society as well as physical and mental fitness. The women who joined the police force expected to play varied roles, resulting into dual-role conflict. The multiplicity of her roles brings a lot of confusion with regard to her role and status. The present investigation tried to find of the relationship between psycho social support and sociodemographic factors among the women police force in India, especially the women police force in Virdhunagar district, Tamil Nadu